Cost-effectiveness analysis of tislelizumab plus chemotherapy as the first-line treatment for advanced or metastatic oesophageal squamous cell carcinoma in China. - Chaoneng He; Xiufang Mi; Gaoqi Xu; Xinglu Xu; Wenxiu Xin; Like Zhong; Junfeng Zhu; Qi Shu; Luo Fang; Haiying Ding (PLoS ONE)
Objective We aimed to investigate the cost-effectiveness of tislelizumab plus chemotherapy compared to chemotherapy alone as a first-line treatment for advanced or metastatic oesophageal squamous cell carcinoma (OSCC). Methods A partitioned survival model was developed to evaluate the cost-effectiveness of tislelizumab plus chemotherapy versus chemotherapy alone in patients with advanced or metastatic OSCC over a 10-year lifetime horizon from the perspective of the Chinese healthcare system. Costs and utilities were derived from the drug procurement platform and published literature. The model outcomes comprised of costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER). One-way and probabilistic sensitivity analyses were conducted to address uncertainty and ensure the robustness of the model. Results Tislelizumab plus chemotherapy yielded an additional 0.337 QALYs and incremental costs of $7,117.007 compared with placebo plus chemotherapy, generating an ICER of $21,116.75 per QALY, which was between 1 time ($12,674.89/QALY) and 3 times GDP ($38,024.67/QALY) per capita. In one-way sensitivity analysis, the ICER is most affected by the cost of oxaliplatin, paclitaxel and tislelizumab. In the probabilistic sensitivity analysis, when the willingness-to-pay threshold was set as 1 or 3 times GDP per capita, the probability of tislelizumab plus chemotherapy being cost-effective was 1% and 100%, respectively. Conclusion Tislelizumab plus chemotherapy was probably cost-effective compared with chemotherapy alone as the first-line treatment for advanced or metastatic OSCC in China.